Peptide Inhibitor of Complement C1, a Novel Suppressor of Classical Pathway Activation: Mechanistic Studies and Clinical Potential - Sharp, Julia A.; Whitley, Pamela H.; Cunnion, Kenji M.; Krishna, Neel K. (Frontiers in Immunology, 2014)
The classical pathway of complement plays multiple physiological roles including modulating immunological effectors initiated by adaptive immune responses as well as an essential homeostatic role in the clearance of damaged self-antigens. However, dysregulated classical pathway activation is associated with antibody-initiated, inflammatory diseases processes like cold agglutinin disease (CAD), acute intravascular hemolytic transfusion reaction (AIHTR) and acute/hyperacute transplantation rejection. To date, only one putative classical pathway inhibitor, C1 esterase inhibitor (C1-INH), is currently commercially available and its only approved indication is for replacement treatment in hereditary angioedema (HAE), which is predominantly a kinin pathway disease. Given the variety of disease conditions in which the classical pathway is implicated, development of therapeutics that specifically inhibit complement initiation represents a major unmet medical need. Our laboratory has identified a peptide that specifically inhibits the classical and lectin pathways of complement. In vitro studies have demonstrated that these Peptide Inhibitors of Complement C1 (PIC1) bind to the collagen-like region of the initiator molecule of the classical pathway, C1q. PIC1 binding to C1q blocks activation of the associated serine proteases (C1s-C1r-C1r-C1s) and subsequent downstream complement activation. Rational design optimization of PIC1 has resulted in the generation of a highly potent derivative of fifteen amino acids. PIC1 inhibits classical pathway mediated complement activation in ABO incompatibility in vitro as well as inhibiting classical pathway activation in vivo in rats. This review will focus on the pre-clinical development of PIC1 and discuss its potential as a therapeutic in antibody-mediated classical pathway disease, specifically AIHTR.